MANAJEMEN PEMBELAJARAN MATA KULIAH KEWARGANEGARAAN DAN MODERASI BERAGAMA PADA PROGRAM STUDI MPI, TBG, DAN PAI IAIN PALANGKA RAYA - Khoirunisa, Aminah; Ahmadi, Ahmadi (Jurnal Manajemen Pendidikan, 2025)
This research aims to look at the learning management of Citizenship and Religious Moderation courses in the MPI, TBG and PAI study programs at IAIN Palangka Raya. Management research is new ideas, practices, objects and methods in the field of education to achieve educational goals or solve educational problems. The new ideas, practices and methods referred to are something that is already running, already exists, has been put into practice in the daily management process within the framework of improving the quality of education. By using a qualitative approach and taking research locations in the MPI, TBG and PAI IAIN Palangka Raya study programs. Data in this service is divided into two types, namely primary and secondary data. Primary data was collected by conducting unstructured interviews with the Head of the Study Program and the supporting lecturers who were appointed as informants. Secondary data is arranged in the form of documents. Secondary data is obtained from the documentation process during observations and other documents that support research. The data collection techniques use interview, observation and documentation techniques. Meanwhile, carrying out data analysis includes data reduction, data presentation and drawing conclusions.